EVALUATION OF THE CANADIAN CT HEAD RULE FOR ANALYZING DIAGNOSTIC ACCURACY IN PATIENTS WITH MINOR HEAD TRAUMA - Kızılgöz, Volkan; Avcı, Sema; Sivrioğlu, Ali Kemal; Aydın, Hasan; Çetin, Türkhun; Kızılgöz, Berihat (Malang Neurology Journal, 2019)
Background: Head computed tomography (CT) scans, which provide reliable information to assessor rule out neurological abnormalities and injuries, should be used judiciously to minimize radiation exposure and cost. Objective: The aim of this study was to evaluate the widely used Canadian CT Head Rule (CCHR) to determine the necessity of head CT scans in patients with minor head trauma.Methods: This retrospective study included 913 patients with head trauma who were admitted to Harakani State Hospital between June 2014 and December 2017. The patient data were reevaluated according to CCHR and compared with the radiological findings. Results: There were a total of 556 patients fulfilling the inclusion criteria with a male/female ratio of 2.95 and a mean age of 37 ± 4.24 years. The most common injury mechanism of head trauma wasmotor vehicle accidents. Chi square tests were applied for statistical calculations. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy of the CCHR were 93%, 88%, 88%, 94%, and 90%, respectively.Conclusion: CCHR was highly useful for patients with minor head trauma who could benefit from head CT evaluation with high sensitivity and specificity.